Posibilities of Developments of Financial System in Lithuania - Rutkauskas, Aleksandras Vytautas; Vilkancas, Renaldas (Ekonomika, 1995)
The current monetary and financial structure of the World economy differs dramaticaly in many eany ways from just a few years ago. Moreover, significant change continues to occur, in today’s quikly changing economic and social enivironment. Economists believe that changes in financial system and movements in economic activity are closely related. What happens in financial system has a poverfull impact upon the health of the nation’s economy. For this reason we obviously are interested in the nature and strength of the country’s financial system and its development trends. Some issues of development of world financial system is discused in this presentation as well as possible trends of further development of Lithuanian financial system.